2017
DOI: 10.1021/acsomega.7b00347
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pseudoisocytidine Tautomerization in Triplex-Forming Oligonucleotides: In Silico and in Vitro Studies

Abstract: Pseudoisocytidine (ΨC) is a synthetic cytidine analogue that can target DNA duplex to form parallel triplex at neutral pH. Pseudoisocytidine has mainly two tautomers, of which only one is favorable for triplex formation. In this study, we investigated the effect of sequence on ΨC tautomerization using λ-dynamics simulation, which takes into account transitions between states. We also performed in vitro binding experiments with sequences containing ΨC and furthermore characterized the structure of the formed tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…In addition, the contribution of tautomeric forms that are unproductive for binding in the ψ C base further diminish stability. [ 116 ] The native bases are unique in their relative chemical stability and tautomeric purity; unnatural WC‐shuffled bases like those examined by Benner and coworkers are limited to some degree by the contribution of nonproductive tautomers [ 59 ] and can be susceptible to epimerization, oxidation and hydrolysis. [ 66 ] Benner has reported that one such WC‐shuffled base, [ 117 ] a pyrazine derivative (pyDDA) mimicking C + , can target the GC base pair via the purine Hoogsteen face [ 118 ] at neutral pH (Figure 5).…”
Section: Unnatural Bases In Noncanonical Interactionsmentioning
confidence: 99%
“…In addition, the contribution of tautomeric forms that are unproductive for binding in the ψ C base further diminish stability. [ 116 ] The native bases are unique in their relative chemical stability and tautomeric purity; unnatural WC‐shuffled bases like those examined by Benner and coworkers are limited to some degree by the contribution of nonproductive tautomers [ 59 ] and can be susceptible to epimerization, oxidation and hydrolysis. [ 66 ] Benner has reported that one such WC‐shuffled base, [ 117 ] a pyrazine derivative (pyDDA) mimicking C + , can target the GC base pair via the purine Hoogsteen face [ 118 ] at neutral pH (Figure 5).…”
Section: Unnatural Bases In Noncanonical Interactionsmentioning
confidence: 99%
“…Previous studies have indicated that due to tautomeric forms, J may form stable J-G base pairs (Figure 4a). 36 We propose that M disfavors Watson−Crick pairing with G because it forms only two hydrogen bonds in the unprotonated state and has repulsive interactions when protonated (Figure 4a).…”
Section: ■ Resultsmentioning
confidence: 98%
“…This could be due to the ability of the pseudoisocytidine base to tautomerize such that N3 would be either a hydrogen bond donor or acceptor (Figure S2c). These results suggest that base-flipping by ADAR2 is most efficient when a complementary hydrogen bond donor–acceptor pair exists between residue 488 and N3 of the orphan base.…”
Section: Resultsmentioning
confidence: 99%